HIV – A Dental Perspective - O’Halloran, Michael (Trinity Student Medical Journal, 2005)
The treatment of patients infected with HIV (human immunodeficiency virus) is a very interesting discipline within both medicine and dentistry. Recent advances in antiretroviral therapies have resulted in infected patients now having much longer symptom-free life spans and treatment planning now challenges the clinician to be cognisant of all the oral and dental aspects of the disease and its treatment. As well as influencing the epidemiology of the classical HIV-related lesions and infections, these drugs are associated with many drug interactions and adverse side effects. This review aims to describe the significant oral manifestations of the disease and highlight difficulties in managing this subset of patients.